(untitled) (Orfeu, 2020)
This paper is part of the undergraduate research on the use of timelines in three pieces of the album “Coisas” (1965), byBraziliancomposerMoacirSantos, presented at FAP/UNESPAR (Curitiba, Brazil), in 2019. The present study is based on the rhythmic aspect, drawing attention to the vertical perspective of the pieces, the polyrhythmic textures and the contrasts between the musical ideas articulated by MoacirSantos. The aim is to demonstrate, especially in “Coisa nº 5”, the strong influence of African matrix through timelines, based on the original recording and the score book “Coisas: cancioneiro Moacir Santos”. Thus, the analyses show that the identified timelines are customized, creating combinations with the function of guidingtherhythmic structureofthepiece.